Reflection of Psychological Analysis in the Main Character of Emil Scherbe’s “Nameless Monster” - Nafiah, Homsatun; Sulastri, Sulastri (Teaching English and Language Learning English Journal, 2025)
Short story is one of fictional prose forms that typically focus on a single event and limited character development. This research aims to analyze psychological aspects through languages experienced by the main character in the short story “Nameless Monster” by Emil Scherbe. The data were employed from the words, phrases, or sentences containing the psychological representation in the story. The theory used in this research was Sigmund Freud’s psychological theory of personality. In conducting this research, the methodology was qualitative and presented descriptively. The results of this research revealed that two stages namely id and ego briefly and strongly performed by the main character, while the superego is almost completely absent from the story. Finally, even though the subject is a non-human creature, analyzing psychological features in the short story contributes to criticize how language is used to express ideas and feelings, also to create certain effects including emotion.